THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY AND TRUST ON CUSTOMER SATISFACTION AT BANK BENGKULU TAIS BRANCH - Dodi Asmawi; Ida Anggriani; Nia Indriasari (Utan Kayu Publishing, 2024)
This study aims to determine the effect of product quality, service quality and trust on customer satisfaction at Bengkulu Bank Tais Branch both partially and simultaneously. The analysis method used is validity test, reliability test, multiple linear regression, coefficient of determination, t test and F test. The data collection method uses a questionnaire. The sample in this study amounted to 80 customers of Bank Bengkulu Tais Branch. Based on the results of research and discussion, it is found that product quality partially has a significant effect on customer satisfaction at Bengkulu Bank Tais Branch because the significant value is 0.000 0.05. Service quality partially has a significant effect on customer satisfaction at Bengkulu Bank Tais Branch because the significant value is 0.028 0.05. Trust partially has a significant effect on customer satisfaction at Bengkulu Bank Tais Branch because the significant value is 0.001 0.05. Product quality, service quality and trust simultaneously have a significant effect on customer satisfaction at Bengkulu Bank Tais Branch because the significant value is 0.000 0.05. Given that product quality, service quality and trust have a significant effect both partially and simultaneously on customer satisfaction at Bank Bengkulu Tais Branch, it is hoped that Bank Bengkulu Tais Branch will continue to improve the quality of its products and services and continue to strive to foster customer trust in Bank Bengkulu Tais Branch, this is so that customer satisfaction can continue to increase so that customers will remain loyal / loyal because they are satisfied with the performance of Bank Bengkulu Tais Branch.